Clinician perception of long‐term survival at the point of critical care discharge: a prospective cohort study. (4th May 2020) - Morton, B.; Penston, V.; McHale, P.; Hungerford, D.; Dempsey, G.
Summary: Critical care survivors suffer persistent morbidity and increased risk of mortality as compared with the general population. Nevertheless, there are no standardised tools to identify at‐risk patients. Our aim was to establish whether the Sabadell score, a simple tool applied by the treating clinician upon critical care discharge, was independently associated with 5‐year mortality through a prospective observational cohort study of adults admitted to a general critical care unit. The Sabadell score, which is a measure of clinician‐assigned survival perception, was applied to all patients from September 2011 to December 2017. The primary outcome was 5‐year mortality, assessed using a multivariable flexible parametric survival analysis adjusted for baseline characteristics and clinically relevant covariates. We studied 5954 patients with a minimum of 18 months follow‐up. Mean (SD) age was 59.5 (17.0) years and 3397 (57.1%) patients were men. We categorised 2287 (38.4%) patients as Sadabell 0; 2854 (47.9%) as Sadabell 1; 629 (10.5%) as Sadabell 2; and 183 (3.1%) as Sadabell 3. Adjusted hazard ratios for mortality were 2.1 (95%CI 1.9–2.4); 4.0 (95%CI 3.4–4.6); and 21.0 (95%CI 17.2–25.7), respectively. Sabadell 3 patients had 99.9%, 99.5%, 98.5% and 87.4% mortality at 5 years for patients in the age brackets ≥ 80, 60–79, 40–59 and 16–39 years, respectively. Sabadell 2 patients had 71.0%, 52.7%, 44.8% and 23.7% 5‐year mortality for these same age categories. The Sabadell score was independently associated with 5‐year survival after critical care discharge. These findings can be used to guide provision of increased support for patients after critical care discharge and/or informed discussions with patients and relatives about dying to ascertain their future wishes.